Platelet concentrate collection in a dual-stage channel using computer-generated algorithms for collection and prediction of yield - Hester, Jeane P.; Ventura, Gerard J.; Boucher, Terry (Plasma therapy & transfusion technology, 1987)
The automated collection of single-donor platelet concentrates is described for a dual-stage channel mounted in a continuous-flow cell separation system (Spectra). Research objectives included collection of a predicted yield of leukocyte-and erythrocyte-poor platelet concentrates using computer-controlled flow rates of anticoagulated whole blood and its separated components (packed erythrocytes, platelet-poor plasma, and platelet concentrates). To achieve these objectives, mathematic algorithms were generated that integrated the known major biologic and procedural contributions to platelet harvesting with the design characteristics of the channel in which blood was to be processed. Data to compute these algorithms are entered into the computer prior to the collection procedure. It was perceived that the ability to predict platelet yield would provide a tool for collecting specific cell quantities for transfusion for a given recipient. A theoretical immunologic benefit to patients receiving lymphocyte-poor platelet concentrates is postulated but remains to be established. An additional objective was that of flexibility so that the predicted yield could be collected based on either volume requirements (for pediatric patients or patients with volume restrictions) or platelet concentration requirements (for storage). The following data summarize the results of some 100 research procedures conducted with this system.